Acceptability and effectiveness of a monofilament, polyethylene insecticide-treated wall lining for malaria control after six months in dwellings in Vhembe District, Limpopo Province, South Africa. (December 2015) - Kruger, Taneshka; Sibanda, Mthokozisi; Focke, Walter; Bornman, Maria; Jager, Christiaan
Abstract Background South Africa uses indoor residual spraying (IRS) for vector control in its malaria control programme (MCP). Insecticide-treated wall linings (ITWLs) offer possible advantages over IRS and long-lasting, insecticide-treated nets (LLINs). This study assessed the user acceptability and perceived effectiveness, and the durability, including efficacy through bioassays, of a newly developed, monofilament polyethylene ITWL. Methods Four ITWL formulations/treatments, two incorporated with deltamethrin and two with alpha-cypermethrin in concentrations ranging from 0.29 to 0.85 wt%, and untreated linings were randomly installed on the inner walls of traditional mud huts (n = 20) and modern brick houses (n = 20) in a community village in Vhembe District, Limpopo Province. The linings were exposed to conditions within these dwellings over 6 months. Data were collected monthly through questionnaires and entomological residual efficacy analysis of ITWL, as part of durability testing, was done bimonthly using WHO prescribed bioassays. Results Monofilament polyethylene ITWLs were successfully installed in traditional sleeping huts and in bedrooms of modern type brick houses. ITWL remained intact throughout the entire 6 months of the study. Participants did not express any dissatisfaction towards the linings although two participants indicated the product should be fitted at a lower level for better results. User perceived effectiveness was very high with participants reporting observed mortality of mosquitoes and other nuisance insects. This perception coincided with results obtained through residual efficacy bioassays where a 100 % knockdown and mortality of mosquitoes was recorded throughout the trial period. Acceptability regarding appearance, including colour, position and attachment method, was also satisfactory with some participants citing the lining as decorative. All participants opted to keep ITWL and residual long-term efficacy will be determined annually for a further 3 years. Conclusions The newly developed ITWLs are highly accepted amongst participants in an unsprayed section of a village in a malaria-endemic area. The perceived effectiveness that coincides with results obtained through bioassays and acceptance of the overall appearance of ITWL will be evaluated over a longer term to determine sustainability. With further developing and testing, this ITWL has the potential to become a sustainable and safer alternative vector control method.